Concussion reporting, return to learn, and return to play experiences in a sample of private preparatory high school students. (28th July 2020) - Waltzman, Dana; Daugherty, Jill; Snedaker, Katherine; Bouton, Jason; Wang, David
ABSTRACT: Objective: The objective of this study is to describe concussion reporting and return to learn and play among high school students. Methods: Self-reported survey data of 1, 999 New England private preparatory high school students who played sports or engaged in recreational activities were collected in 2018. Descriptive and bivariate statistics are presented. Results: Three in ten respondents (31.4%) reported ever sustaining a concussion and 22.0% did not report at least one concussion to an adult. The most common reasons for not reporting included wanting to keep playing their sport (58.0%) and not thinking the injury was that serious (53.6%). Girls and students in higher grades took longer to return to school and sports. A quarter of students reported pretending to have a faster recovery in order to return to school or sports. Conclusion: Private school students who play sports or engage in recreational activity may be at risk of sustaining concussions and may not report their symptoms due to a lack of understanding the seriousness of concussion, not wanting to fall behind in school, or out of desire to continue playing their sport. Teachers, coaches, and parents can stress reporting as the first step in recovery.